Therapeutic effects of aqueous extract of aerial parts of Teucrium polium L. against acrylamide-induced thyro-reprotoxicity in male rats - Farida DAOUDI; Djahida MAHDI; Leila BEDDAR (Notulae Scientia Biologicae)
Acrylamide (ACR) is a toxic chemical found in food and the environment. Medicinal traditional plants are used as alternatives to attenuate the adverse effects of many hazardous chemicals on human health. This study investigated the protective effects of prepared traditional aqueous extract of aerial parts of Teucrium polium L. (T. polium) on ACR-induced thyro-reprotoxicityin male rats. In this study, 24 rats were distributed into four equal groups and treated orally for 21 days. The first group was the control; the second and third groups received ACR (20 mg/kg/bw) and T. polium (400 mg/kg/bw), respectively; and the fourth group received T. polium and ACR. ACR caused a significant decrease in daily body weight and no changes in testes and epididymis relative weights. Compared to controls, ACR triggered hypothyroidism, as shown by a significant decrease in triiodothyronine and thyroxine plasma levels and thyroid histopathology. Most of thyroid follicles were hypertrophied; other follicles degenerated, and their form changed with the absence of colloid and fusion of the follicles, while others appeared with multiple layers that obliterated the lumen, and others were infiltrated by inflammatory cells. Moreover, ACR caused atrophy and severe degeneration in both seminiferous and epididymal tubules. The majority of these tubules were empty and devoid of spermatozoa.  ACR also significantly decreased testosterone levels, sperm concentration, motility, and vitality. However, all deleterious effects of ACR were ameliorated following the administration of T. polium. The aerial parts of aqueous extract of T. polium provide substantial protection against ACR-induced thyro-reprotoxicity, thus improving male fertility and reproduction.